An Experimental Examination of the Interaction between Mood Induction Task and Personality Psychopathology on State Emotion Dysregulation - Borges, Lauren M. (Behav Sci (Basel), 2015)
While emotion dysregulation has been investigated as a key variable in the development and persistence of personality psychopathology, few studies have explored state emotion dysregulation among individuals with personality disorders (PDs). The current study addresses this void in the literature through a laboratory investigation of state emotion dysregulation among participants with and without PDs. To facilitate this goal, participants were matched to pairs based on similar personality features and were randomized to one of two behavioral analogues; either the Paced Auditory Serial Addition Task-Computerized (PASAT-C) or an interpersonally based mood induction. As hypothesized, PD participants in the PASAT-C reported significantly more difficulty with impulsivity and emotion regulation strategies. Contrary to expectations, the PD group in the interpersonal task demonstrated significantly less difficulty with non-acceptance of emotion and emotional clarity and significantly greater positive affect compared to non-PD participants. Implications for these findings and directions for future research are discussed.